Pemetaan Situasi Skala Besar (1:500) Kampus Politeknik Negeri Batam - Farouki Dinda Rassarandi; Oktavianto Gustin; Sudra Irawan; Wenang Anurogo; Siti Noor Chayati; Rizki Widi Pratama; Fajar Putra; Rafly Aditia; Melia Wandanita (JURNAL INTEGRASI, 2022)
A situation map is large-scale topographic map which is a presentation of description of the earth’s surface, both natural and man-made, drawn on a flat (paper) plan with a projection system and certain scale. A situation map can be obtained by terrestrial mapping, which is a mapping process in which measurements are made directly on the earth’s surface with certain measuring equipment. 1:500 scale situation map creation through terrestrial measurement and depiction using digital technology. The stages in making a situation map begin with the creation of a basic mapping framework which includes measurements of the Horizontal Control Framework (KKH) and Vertical Control Framework (KKV), then proceed to the stage of measuring detailed points which include planimetric and height details, calculating the measurement data, and digital map creation using SIG processing software. The measurement data is realized in the form of a 1:500 scale situation map located in the Polibatam campus area, Teluk Tering, Batam Kota, Kota Batam which is then printed on A3 size paper. This situation map contains information about contours or elevations, several spatial and building situations or existing in the Polibatam campus area which is used as the basis or regional landscapes to support the development of the new Polibatam lecture building. Which from the results of detailed data processing and this situation there are contours or the highest elevation is located to the north of the main building of the Batam State Polytechnic which is as high as 40 m above sea level and the lowest elevation is located to the southeast of the Batam State Polytechnic male dormitory as high as 34 m above sea level, which is the location is a swamp which is basically a mud type soil.